O coordenador pedagógico e as relações afetivas promotoras de desenvolvimento - Volpe, Tatiana Alves Lara (2019)
The present work had as objective to analyze what professional knowledge the pedagogical coordinator (PC) mobilizes with focus in the continuous formation for the management of interpersonal relations in order to contribute to the good functioning of the school. The specifics objectives were: to identify characteristics of the interpersonal relations between PC and teachers that are facilitators for the performance of their functions; to identify what knowledge the coordinator uses when it comes to issues related to interpersonal relationships in the school and to reflect on the importance of good interpersonal relationship between PC and teachers as a condition for a school-centered formation. The research, of a qualitative approach, based on the study of the situations, practices and relations that constitute the experiences, involved three pedagogical coordinators of a municipality of the great São Paulo. The information was produced through questionnaire and interview. The theoretical basis of the research is based mainly on the studies of Placco, Almeida, Rogers and Wallon, and others that have been working with the role of pedagogical coordinator and interpersonal relationships in school. The analysis showed that the work of the PC does not only imply the management of tasks, but especially in the management of relations. The interviewees' speech reveals that it is in the possibility of living together, by experiencing interpersonal relationships and seeking alternatives to solve situations of conflict, that professionals have the possibility to turn to themselves and change. The analysis also pointed out that training and experience are fundamental to the good performance of the pedagogical coordinator, since it is he who articulates those involved in the teaching-learning process, being able to maintain interpersonal relations in a healthy way, valuing the teacher's formation and his and creating strategies to deal with differences, with the main objective of collaborating effectively in the construction of a quality education. Finally, having a relational ability, being sensitive to the needs of the other, believing in your group, watching and listening carefully to what the group has to say, including their expectations regarding the work of the PC